2016
DOI: 10.1148/radiol.2016151029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bowel Wall Enhancement for the Diagnosis of Intestinal Ischemia in Patients with Small Bowel Obstruction: Value of Adding Unenhanced CT to Contrast-enhanced CT

Abstract: Purpose To determine whether adding unenhanced computed tomography (CT) to contrast material-enhanced CT improves the diagnostic performance of decreased bowel wall enhancement as a sign of ischemia complicating mechanical small bowel obstruction (SBO). Materials and Methods This retrospective study was approved by the institutional review board, which waived the requirement for informed consent. Two gastrointestinal radiologists independently performed retrospective assessments of 164 unenhanced and contrast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…14, so we could have misinterpreted the degree of enhancement if hemorrhage and congestion were already present before contrast agent administration. Indeed, Chuong et al (28) recently showed that adding an unenhanced phase to the contrastenhanced phase could improve diagnostic confidence and interobserver agreement for evaluation of this CT sign. Decreased bowel enhancement remains an independent CT sign associated with irreversible bowel ischemia (positive predictive value, 65%; 95% CI: 48%, 85%).…”
Section: Discussionmentioning
confidence: 99%
“…14, so we could have misinterpreted the degree of enhancement if hemorrhage and congestion were already present before contrast agent administration. Indeed, Chuong et al (28) recently showed that adding an unenhanced phase to the contrastenhanced phase could improve diagnostic confidence and interobserver agreement for evaluation of this CT sign. Decreased bowel enhancement remains an independent CT sign associated with irreversible bowel ischemia (positive predictive value, 65%; 95% CI: 48%, 85%).…”
Section: Discussionmentioning
confidence: 99%
“…Performing both unenhanced and contrast-enhanced CT improves test sensitivity, diagnostic confidence, and interobserver agreement in the diagnosis of ischemia. Decreased or absent mural enhancement after administration of IV contrast is a useful, highly specific, indicator of intestinal ischemia (95-100%), despite variable sensitivity of 40-60% [46,57,58]. A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60].…”
Section: Abdominal Ctmentioning
confidence: 99%
“…A recent meta-analysis showed that decreased mural enhancement was more predictive of ischemia than any other single CT sign [59,60]. This sign was 100% specific and 56% sensitive for bowel ischemia [57][58][59][60]. Other CT signs of ischemia include bowel wall thickening and mucosal thumbprinting from intramural edema, inflammation, or hemorrhage; pneumatosis intestinalis from intramural gas produced by bacteria; and streaky mesentery from adjacent inflammatory infiltration as listed in Table 2 [11•, 24].…”
Section: Abdominal Ctmentioning
confidence: 99%
“…To date, CT is the preferred imaging technique, and decreased bowel enhancement on CT, which is defined as decreased or absent enhancement after administration of contrast material, is considered the most useful finding to detect the bowel wall ischemia. This finding has a specificity of 95–100% but a variable sensitivity of 33%–78% [11] . In addition, decreased enhancement of the bowel wall during the arterial phase is difficult to evaluate, considering the rate of interobserver agreement [12] .…”
Section: Discussionmentioning
confidence: 94%